A ação empreendedora na gestão pública escolar - Nascimento, Priscilla Oliveira (2018)
This work searched for doing an investigation about the entrepreneurial action from public management at the schools. In this way, this research was produced in article fo rmat being the first a theoretical work, the second an empirical study and the third a technical product present as a guidebook of good practice to the school management. At first, was produced a theoretical work that pro posed a theoretical scheme to understand the entrepreneurial as from the entrepreneurial action with the intention to conceptualize the entrepreneurial over from individual focus, trying to explore the interaction between people, organization and society. It is to consider that the interaction between them it’s possible to change the actual framework through the creativity and innovation. Broaden the field of vision from the entrepreneurial to simplify the understanding of it. As result was presented the entrepreneurial action cycle, through it is possible to understand this phenomenon empirically. The second article identifies four entrepreneurial actions at the school management context from a city located at Minas South, of which should be linked to the National Education Plan. The identifiedentrepreneurialactions showed the public managers search to establishing from competent school management which circumvent the faced tensions and redirect the action flow and, at the same time, implement the innovative actions that enable the attendance of public interest. As a technical product, for the reason that this research comes from a professional master program, was produced a guidebook of good practice to the school management, that spread new knowledges to face with social, economic, politic and management problems that are common among the public managers. The guidebook was made to provide direction and to inspire the daily questions that school managers face with, and through this guidebook it is possible t o find solutions to them. Therefore, through this research was possible to identify that, despite the peculiarities and characteristics from the investigated cities, in general, all of them present very similar problems and, each one at its way, tried to create mechanisms to deal with these adversities. In this way, this research showed that, although the Brazilian public management is a challenging and bumpy task, in front of the hybridity of the management and the simultaneous patrimonial, bureaucratic, managerial and societal practices existence, the diversity of actors in the Brazilian public management could enable the entrepreneurial actions occurrence, resulting in an increase from its efficacy, in other words, through the people, institutions and soc iety interlacing that emerges the entrepreneurial actions, without special people and heroic deeds, treating from a situated creativity process.